2019
DOI: 10.5194/bg-2019-245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methane production by three widespread marine phytoplankton species: release rates, precursor compounds, and relevance for the environment

Abstract: <p><strong>Abstract.</strong> The world’s oceans are considered to be a minor source of methane (CH<sub>4</sub>) to the atmosphere although the magnitude of total net emissions is highly uncertain. In recent years the origin of the frequently observed in situ CH<sub>4</sub> production in the ocean mixed layer has received much attention. Marine algae might contribute to the observed CH<sub&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Methane production has been reported during growth of coccolithophores 13 and other ubiquitous members of the prymnesiophyte class of marine phytoplankton 43 , which may contribute in part to the correlation we find between ∆CH 4 and NPP. However, a number of alternative pathways have been proposed for methanogenesis in surface ocean waters, which could give rise to the relationship indirectly.…”
Section: Discussionsupporting
confidence: 54%
“…Methane production has been reported during growth of coccolithophores 13 and other ubiquitous members of the prymnesiophyte class of marine phytoplankton 43 , which may contribute in part to the correlation we find between ∆CH 4 and NPP. However, a number of alternative pathways have been proposed for methanogenesis in surface ocean waters, which could give rise to the relationship indirectly.…”
Section: Discussionsupporting
confidence: 54%
“…Currently, there are two proposed pathways for oxic‐lake water CH 4 production: (1) Methane as a by‐product of methylphosphonate (MPN) decomposition, which is an alternative way of phosphorus acquisition when inorganic phosphorus is limited (Carini et al 2014; Yao et al 2016; Wang et al 2017); and (2) a pathway independent of MPN demethylation which is thought to be based on a Coenzyme‐M homologue (Tang et al 2016). Several studies have demonstrated the involvement of photoautotrophs in CH 4 formation in oxic water, both in the field (Grossart et al 2011; Bogard et al 2014; Hartmann et al 2020) and in the laboratory (Lenhart et al 2016; Klintzsch et al 2019; Bizic et al 2020; Hartmann et al 2020). The association of oxic CH 4 production to MPN degradation and autotrophic organisms suggests that phosphorus and light might be important factors driving oxic CH 4 production.…”
mentioning
confidence: 99%
“…Recent experimental observations indicate that [FeFe]‐nitrogenase from Rhodopseudomonas palustris can release methane directly from bicarbonate (Zheng et al, ), though the flux would be small and these organisms are vastly outnumbered by SAR11 (Carlson et al, ). Finally, haptophyte algae and coccolithophores were shown to demethylate common methyl‐bearing compounds such as dimethyl sulfoxide, dimethyl sulfide, methionine sulfoxide, methionine, and dissolved inorganic carbon (Bizic‐Ionescu et al, ; Klintzsch et al, ; Lenhart et al, )—though each of these processes necessitates full isotopic characterization before it can be included or excluded in interpreting methane cycling in oxic waters, and it is not clear how large these fluxes would be in a system such as ALOHA given the more clear inorganic P‐limited scenario. Taken together, we infer that methane in surface waters at Station ALOHA reflects the carbon isotope delta values of MPn in HMWDOM and precursors in bulk organic matter, while the carbon isotopes of methane below the euphotic zone reflect a more complex life history.…”
Section: Resultsmentioning
confidence: 99%
“…Although MPn demethylation is a possible methane source in phosphate‐limited oxygen‐rich systems, directly linking methane to MPn has remained a challenge. Moreover, distinguishing MPn‐derived methane from other known and putative sources (cf Bizic‐Ionescu et al, , Klintzsch et al, , Zheng et al, ) requires each process generate unique fractionation patterns. The stable isotopes of carbon (C) and hydrogen (H) within the methane have been used to track biotic and abiotic sources across a diversity of environments and processes (Etiope & Sherwood Lollar, ; Whiticar et al, ).…”
Section: Introductionmentioning
confidence: 99%